Quantity and quality of environmental disclosure by environmental sensitive companies in Malaysia - Mohd Said, Ridzwana; Kim, Lee Liu; Senik, Rosmila; Yusri, Yusniyati (Medwell Online, 2016)
This study examines the level of environmental information disclosure in the annual reports of 150 environmentally sensitive companies in Malaysia for the year 2012. Interpretative content analysis is used to examine the quantity and quality of the environmental disclosure against the global reporting initiative environmental performance indicators. The findings revealed that the level of environmental disclosure by sampled companies is limited and mostly in declarative form. Very few companies disclose comprehensive information in their annual reports. This study contributes to the current literature of environmental reporting and suggests regulators to strengthen the enforcement upon companies to report more comprehensive environmental information